2022
DOI: 10.14254/2071-8330.2022/15-3/6
|View full text |Cite
|
Sign up to set email alerts
|

Methods for risk premium: Application for agriculture companies in Czech Republic

Abstract: In business valuation, alternative cost of equity plays an important role considering the risk related to investment. Even a slight change in cost of equity can significantly affect the resulting business value. However, in the Czech Republic, risk premium has not been adequately addressed in terms of methodology. The objective of the paper is to explore the application of selected methods in calculating risk premium, and to select or modify existing methodology for the calculation of risk premium used in agri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
1
0
1
Order By: Relevance
“…By contrasting the Build Up model, CAPM, and Fama and French Three Factor Model, Machova et al researched the various approaches to determining risk premiums for farm enterprises in the Czech Republic and concluded that the Build Up model is the most appropriate [7]. Using the panel regression approach, Gharaibeh, and AL-Tahat researched the variables that affected the capital structures of service companies in Jordan in the past 4 years since 2018.…”
Section: Related Researchmentioning
confidence: 99%
“…By contrasting the Build Up model, CAPM, and Fama and French Three Factor Model, Machova et al researched the various approaches to determining risk premiums for farm enterprises in the Czech Republic and concluded that the Build Up model is the most appropriate [7]. Using the panel regression approach, Gharaibeh, and AL-Tahat researched the variables that affected the capital structures of service companies in Jordan in the past 4 years since 2018.…”
Section: Related Researchmentioning
confidence: 99%
“…La investigación methods for risk premium: Application for agriculture companies in Czech Republic, de los autores Machová, Kučera & Kašparová (2022), aborda la importancia del costo alternativo del capital en la valoración de empresas y cómo la prima de riesgo juega un papel fundamental en el cálculo de este costo. El objetivo del artículo es explorar diferentes métodos para calcular la prima de riesgo y seleccionar el más adecuado para las empresas agrícolas en la República Checa.…”
Section: Revisión De La Literaturaunclassified